2010
DOI: 10.1016/j.neubiorev.2009.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological biomarkers explaining the association between depression and prognosis in coronary artery patients: A critical review of the literature

Abstract: This paper aims to provide an overview of the current state of affairs on psychophysiological factors that may explain the link between depression and adverse outcome in coronary artery disease (CAD) patients. Factors discussed include heart rate variability, inflammation, platelet function, hypothalamus-pituitary-adrenal axis activity, serotonin metabolism and polyunsaturated fatty acids. Evidence suggests the involvement of each of these factors in both depression and CAD, together contributing to the prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 98 publications
0
65
0
1
Order By: Relevance
“…These associations are largely independent of markers of disease severity and cardiovascular risk profiles (Kronish et al 2009). Investigation of the mechanisms relating depression with future cardiovascular morbidity is an active field of research, with candidates including biological processes such as autonomic, inflammatory, neuroendocrine and endothelial dysfunction, together with deficits in adherence to medication and life-style advice (Grippo & Johnson, 2009 ;de Jonge et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These associations are largely independent of markers of disease severity and cardiovascular risk profiles (Kronish et al 2009). Investigation of the mechanisms relating depression with future cardiovascular morbidity is an active field of research, with candidates including biological processes such as autonomic, inflammatory, neuroendocrine and endothelial dysfunction, together with deficits in adherence to medication and life-style advice (Grippo & Johnson, 2009 ;de Jonge et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been found to have a negative influence on cardiac prognosis (van Melle et al, 2004), but the mechanisms of this association remain unclear (de Jonge et al, 2010). Several studies have evaluated the association between depression and inflammatory markers, including interleukin (IL)6, high sensitive C-reactive protein (hsCRP), tumor necrosis factor (TNF)-a and its soluble receptors (Penninx et al, 2003;Whooley et al, 2007;Kupper et al, 2012;Vogelzangs et al, 2012).…”
mentioning
confidence: 99%
“…More recently, it has been suggested that RAGE may form dimers and multimers for ligand binding to occur. 7 A range of splice variants of murine and human RAGE has been identified; most of these lead to removal of the transmembrane domain to produce soluble variants. RAGE has a C-truncated secretory isoform that circulates in plasma and which at least two variants: one secreted from cells, endogenously secreted RAGE (esRAGE), and another one, which formed by proteolytic cleavage, by matrix metalloproteinases from the cell-surface, cleaved-RAGE (cRAGE).…”
Section: Receptor For Advanced Glycation Endproducts(rage)mentioning
confidence: 99%